Deutsche Teil- und Regrammatikalisierung - Askedal, John Ole (Studia Germanica Posnaniensia, 2018)
The present paper deals with some putative cases of so-called ‘halted’ or ‘arrested grammaticalization’ in the history of German. The following phenomena are discussed: Old High German perfect auxiliaries; the modals ‘shall’, ‘will’ and the transformative copula werden as sources of future auxiliaries in Old, Middle and New High German; some shortened verb forms in Middle High German; the Old High German etc. pronoun of identity der selbo used as a demonstrative or personal pronoun; the inflection of determiners, quantifiers and adjectives in New High German; Old High German thô, dô and Middle High German ez as syntactic ‘place-holders’ in sentence-initial position; the syntactic status of the German so-called ‘ethical dative’; and the demise of Old High German -lîhho, Middle High German -lîche as an adverb-forming suffix. It is claimed that certain general language-specific, ‘characterological’ patterns influence the way in which the grammaticalization developments in question are halted or, sometimes, given another direction by way of regrammaticalization.